Splitting right to use the main building for the residential area of PT. Rahman Abadi Sejahtera, Tasikmalaya Regency - Putri, Gessy Andrina; Putrijanti, Aju (Universitas Wiralodra, 2023)
The main building construction permit is an ownership right that can be owned by the developer and cannot be owned by individuals. Generally, limited companies only have a Main Building Permit and cannot directly become property rights because they cannot become objects of property rights. If it is to be sold to consumers, the building permit will be split into separate building permits. This research was conducted through direct interviews with sources and supported by a literature study. The research method used is qualitative, with data analysis carried out qualitatively. The legal sources used include primary legal and secondary legal materials. The research results show the distribution of permits to build the main building for the residential area of ​​PT. Rahman Abadi Sejahtera Tasikmalaya Regency by applicable regulations. The main obstacles to distributing permits to construct the main building include a long process and inaccurate land boundaries when measuring, which results in discrepancies between the results of building measurements and the location of residential plots.